Analysis of knowledge, attitudes and actions related to Kbama Bali in couples of childbearing age in Marga sub-district, Tabanan district - Marhaeni, A. A. I. N; Semadi, I Ketut Putra; Mustika, Made Dwi Setyadhi; Arka, Sudarsana (Technium Sustainability, 2025)
This study analyzes the knowledge, attitudes, and actions of couples of childbearing age (PUS) in Marga Sub-District, Tabanan Regency, regarding Bali Governor Instruction No. 1545/2019 on Krama Bali Family Planning (KBAMA Bali). This policy aims to preserve Balinese cultural identity by encouraging families to have up to four children while maintaining reproductive health standards. Using a descriptive quantitative approach, data were collected through structured interviews and surveys with 99 respondents, selected via accidental sampling. The findings revealed that 33.8% of respondents were unaware of the instruction, largely due to a lack of socialization, while 90.7% expressed support for the policy, primarily for cultural reasons. However, 55.5% of the respondents did not implement the instructions in their family planning decisions, citing economic and health-related constraints. This study suggests that further communication, information, and education (KIE) efforts are required to enhance public understanding and align family planning practices with both cultural preservation and population management objectives. Additionally, a periodic knowledge, attitude, and practice (KAP) evaluation is recommended to assess the effectiveness of the policy across different regions.